(untitled) (Research, Society and Development, 2021)
Introduction: sepsis is a systemic inflammatory disease associated with an infection with severe manifestations that occurs throughout the body. However, this infection does not necessarily have to be everywhere in the body, it may be restricted to just one location, but it may cause an inflammatory response throughout the body to try to control the cause of the infection. corticosteroids in the treatment of sepsis in patients hospitalized in intensive care units (ICU’s). Methodology: this is a descriptive research of the integrative literature review type. The descriptors were crossed in English: "sepsis", "hemodynamic", "corticosteroids" in Portuguese: "sepsis", "hemodynamics", "corticosteroids" and in Spanish: "sepsis", "hemodynamic", "corticosteroids" , in the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services. A total of 24 scientific articles were published for the integrative literature review, published between 2011 and 2021. Results The improvement in survival with corticosteroids may result from the reduction in the duration of shock, severity of inflammation and number of organ dysfunctions. The demonstrated benefits are in agreement with the findings of studies in animals, isolated vascular smooth muscle and inflammatory cells and in healthy volunteers challenged with endotoxin. Hydrocortisone has several benefits in relation to health resources, such as: it is a cheap and safe drug, allows for a shorter stay in the ICU, shorter mechanical ventilation time and faster sepsis resolution. Conclusion: glucocorticoids, especially hydrocortisone, can be used to treat patients with sepsis. According to the literature used, the results are satisfactory and have a costing that is easy to adhere to.